EFFICACY OF SOME PESTICIDES AGAINST THE ADULTS OF TWO SPOTTED RED SPIDER MITE (TETRANYCHUS URTICAE KOCH.) ON ACALYPHA COPPERENCIS L. IN LABORATORY CONDITION - HAZRA, SAMAPIKA; MOHASIN, MID.; BANERJEE, AMITAVA; KARMAKAR, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
A laboratory experiment was carried out to study the efficacy of some synthetic pesticides as well as seed kernel extract against the adults of two spotted red spider mite (Tetranychus articae Koch.) on one of its important ornamental host plant Acalypha copperencis L. The experiment reveals that among the synthetic pesticides used dicofol. 18.5 EC was the Superior while endosulfan 35EC and triazophos 40 EC have been found to possess acaricidal effect also. Neem seed kernel extract was found to be uneffective against this mite species.